2010
DOI: 10.1167/iovs.08-2956
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure, Perfusion Pressure, and Open-Angle Glaucoma: The Los Angeles Latino Eye Study

Abstract: Low diastolic, systolic and mean perfusion pressures, low diastolic blood pressure, and high systolic and mean arterial blood pressures are associated with a higher prevalence of OAG in adult Latinos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
193
6
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(216 citation statements)
references
References 24 publications
10
193
6
7
Order By: Relevance
“…18 This biofeedback system prevents hypotension via the regulation of the ultrafiltration rate and facilitates the protection of the optic nerve from the hazardous effects of hypotension, which can offer protection against ischemia and reperfusion damage in glaucoma patients and individuals prone to glaucoma. 19 Aqueous humor dynamics in a glaucomatous eye differs from the normal eye. This difference is mainly related to the outflow pathways.…”
Section: Discussionmentioning
confidence: 99%
“…18 This biofeedback system prevents hypotension via the regulation of the ultrafiltration rate and facilitates the protection of the optic nerve from the hazardous effects of hypotension, which can offer protection against ischemia and reperfusion damage in glaucoma patients and individuals prone to glaucoma. 19 Aqueous humor dynamics in a glaucomatous eye differs from the normal eye. This difference is mainly related to the outflow pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects were excluded if they met one of the following criteria: (1) presence of retinal disease; (2) previous ocular surgery; (3) family history of glaucoma; (4) best-corrected visual acuity o20/40; (5) IOP of 22 mm Hg or greater; (6) refractive error exceeding a spherical equivalent of 9 diopters or astigmatism of 2 diopters; (7) trabecular meshwork not visible in any quadrant on static gonioscopy; or (8) glaucomatous optic disc changes, such as excavation, thinning, or notching of the neuroretinal rim, and disc hemorrhages.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 In addition to elevated IOP, factors such as ocular blood flow, 3 racial factors, 4 refractive errors, 5 genetic factors, 4 and low cerebrospinal fluid pressure 6 have been associated with the glaucoma pathogenesis. However, IOP is the only modifiable risk factor; IOP lowering is the only proven therapy to prevent or slow down the development or progression of glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…Higher systolic and mean arterial blood pressures were associated with a higher prevalence of POAG in the Los Angeles eye study. [27] The Blue Mountains Eye Study, the Egna-Neumarkt glaucoma study and the Rotterdam Eye Study also found that systemic HTN increases the susceptibility to glaucoma, possibly due to a positive correlation between blood pressure and IOP. [28][29][30] Despite this positive correlation, the actual change in IOP with increasing blood pressure is small.…”
Section: Discussionmentioning
confidence: 97%